Developing Interactive Information Boards as Public Educational Media in Sumberingin Edu-Tourism Village, Tumpang, Malang - Satworo Adiwidodo; Bagus Wahyudi; Pondi Udianto; Kris Witono; Asrori Asrori; Siti Duratun Nasiqiati Rosady (PT. ELSHAD TECHNOLOGY INDONESIA, 2026)
Sumberingin bathing area is one of the landmarks of Wringinsongo Village, Tumpang, Malang, with strong potential as a natural spring-based edu-tourism destination. Previous community service programs have supported this area through the installation of an Archimedes screw turbine micro-hydropower demonstration unit in 2022 and the development of Archimedes dye cafe in 2023, which combines natural tourism with science-based learning. However, the lack of supporting information media has limited visitors' understanding of the working principles and benefits of the mechanical demonstration tools. This community service program aims to strengthen public education facilities by developing and installing interactive information boards at cafe cepat archimedes. The method included identifying educational needs, designing the board layout and content, fabricating the information board, installing it in the tourism area, and integrating QR codes linked to digital learning materials. The information board was designed with ergonomic considerations to ensure clear readability and accessibility for children, students, and adult visitors. The result of this program is the availability of an interactive public information board that connects physical learning media with digital content, including a YouTube-based explanation of the Archimedes water turbine. This facility is expected to improve visitor learning experiences, increase the educational value of the tourism area, and support BUMDes in developing more innovative and sustainable edu-tourism services.